Investigating the role of cathepsins in breast cancer progression: a Mendelian randomization study - Zhou, Shengyi; Sun, Yizhou; Zha, Wenzhang; Zhou, Guangjun (Frontiers in Oncology, 2025)
BackgroundBreast cancer, a major threat to women’s health worldwide, has mechanisms of onset that remain unclear. Within the human lysosomal system, a class of enzymes known as cathepsins exhibit elevated expression levels in various malignant tumors, suggesting that they may play key roles in cancer progression.MethodsThis study employed the two-sample Mendelian randomization (MR) approach to investigate the potential causal relationship between cathepsin levels and the risk of developing breast cancer. Furthermore, we conducted MR analysis using eQTL data to investigate how gene expression, mediated by cathepsins, affects the occurrence of different types of breast cancer and assessed the regulatory effects of cathepsins.ResultsMR analysis revealed that increased levels of cathepsin E are associated with a greater risk of malignant breast tumors (IVW: p = 0.006, OR = 1.103, 95% CI = 1.028–1.184), and increased levels of cathepsin F are associated with an increased risk of in situ breast cancer (IVW: p = 0.031, OR = 1.190, 95% CI = 1.016–1.394). Additionally, cathepsin Z has a protective effect against in situ breast cancer (IVW: p = 0.017, OR = 0.846, 95% CI = 0.737-0.971). Cathepsin E can mediate the effects of APBB1IP, NT5C3B, and ZNF66 on HER2-negative breast cancer, as well as the effects of DHRS9, CDK12, and CD247 on HER2-positive breast cancer. Cathepsin F can mediate the effects of ANXA2R and ZNF605 on in situ breast cancer. Cathepsin Z can mediate the effects of PRX, CRY2, ADCY3, and PELATON on in situ breast cancer.DiscussionThese findings highlight the dual roles of cathepsins as potential risk and protective factors for breast cancer, underscoring their potential in diagnostic and therapeutic strategies.